Preparation of Sulfonated Poly (ethylene-co-tetrafluoroethylene-graft-styrene) Based Polymer Electrolyte Membranes for Fuel Cell by using Gamma Irradiation Technique - A. Suliwarno (PPIKSN-BATAN, 2012)
Poly (ethylene-co-tetrafluoroethylene-graft-styrene-sulfonate) was successfully prepared by irradiation grafting of a styrene monomer into ethylenetetrafluoro-ethylene (ETFE) films and followed by sulfonation of the graft chains. Five film sheets of ETFE which having a size of 3 cm x 8 cm, thickness of 25 µm were packed in vacuum using a Y type tube filled with argon gas. The samples were irradiated using γ-rays with a dose of 15 kGy at 15 kGy/h. The iradiated samples were grafted by using styrene monomer at 60o C for 1, 3, 5, 7 and 9 h, respectively. The grafted samples (ETFE-g-St) were washed with xylene to remove homopolymer of polystyrene, and then its degree of grafting (DG) was determined. Sulfonation was carried out by using 0.2 M chlorosulfonic acid in dichloroethane solution at a water bath of 60oC for 6 h. Sulfonated samples (ETFE-g-St-SO3H) were washed with water to neutralize its acidity, and dried in a vacuum drier at 40oC for 15 h. The dried sample was weighed as sulfonated sample in order to determine the degree of sulfonation (%DS). Membrane properties of EFTE-g-St-SO3H sample such as ion exchange capacity (IEC), proton conductivity in cross direction (σ1), and in-plane direction (σ11) were determined by using a HIOKI-3522 LCR HI tester. Durability test of samples were conducted in hot water and 3% H2O2 respectively.. The proton conductivity measurement and durability of the membrane were compared to Nafion 112® as standard. The experimental results showed that the degree of grafting was increased with time of reaction for copolymerization, while %DS gave excellent results with an average of 92.7%. The IEC value was more affected by the %DG as compared to that of %DS effect. The average of σl value of the sample was 0.055 S/cm, compared to σ1 of Nafion112® that was 0.066 S/cm. The average of σ11 of the sample was 0.18 S/cm, while the σ11 of Nafion 112® was = 0.36 S/cm. The sample of SA004 with 53.49% DG was more stable than both the SA001 (21.48%DG) and SA003 (41.52% DG) in durability’s test of the samples against hot water (334 h resistance). On the peroxides test, all of samples were degraded at 114 h. Received: 20 November 2011; Revised: 28 March 2012; Accepted: 30 April 2012